National Behaviour in Multilateral Military Operations. (May 2018) - Haesebrouck, Tim
What accounts for the diverging contributions to multinational military operations? Over two decades ago, Bennett, Lepgold and Unger published a seminal study that aimed to explain the division of the burdens of the Desert Storm Coalition. This article reviews four recent monographs on national behaviour in multinational operations against the backdrop of their conclusions. While the four reviewed titles suggest that the bulk of the conclusions of Bennett, Lepgold and Unger's study hold beyond the scope of the Desert Storm Coalition, each of them also makes a distinct contribution to the literature. Baltrusaitis offers three excellent case studies on burden sharing in the 2003 Iraq War, Davidson provides essential insights on the impact of alliance value and threat and the studies of Auerswald and Saideman and Mello invoke important domestic variables that were not structurally examined by Bennett, Lepgold and Unger. Altogether, the reviewed titles provide convincing explanations for the behaviour of democratic states in US-led operations. Consequently, the article concludes by arguing that the most promising avenue for future research would be to focus on military operations in which the United States has a more limited role and on the contributions of non-democratic states to multinational operations. Auerswald DP and Saideman SM (2014) NATO in Afghanistan: Fighting Together, Fighting Alone . Princeton, NJ: Princeton University Press. Baltrusaitis DF (2010) Coalition Politics and the Iraq War: Determinants of Choice . Boulder, CO: First Forum Press. Davidson J (2011) America's Allies and War: Kosovo, Afghanistan, and Iraq . Basingstoke: Palgrave Macmillan. Mello P (2014) Democratic Participation in Armed Conflict Military Involvement in Kosovo, Afghanistan and Iraq . Basingstoke: Palgrave Macmillan.